2013
DOI: 10.1002/tox.21904
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterium producing cylindrospermopsin cause histopathological changes at environmentally relevant concentrations in subchronically exposed tilapia (Oreochromis niloticus)

Abstract: The acute toxicity of cylindrospermopsin (CYN) has been established in rodents, based on diverse intraperitoneal an oral exposure studies and more recently in fish. But no data have been reported in fish after subchronic exposure to cyanobacterial cells containing this cyanotoxin, so far. In this work, tilapia (Oreochromis niloticus) were exposed by immersion to lyophilized Aphanizomenon ovalisporum cells added to the aquaria using two concentration levels of CYN (10 or 100 μg CYN L(-1)) and deoxy-cylindrosper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 54 publications
7
21
0
Order By: Relevance
“…The highest liver CYN-immunopositivity correlates with the histopathological lesions described by light and electron microscopy in tilapia ( O. niloticus ) acutely and sub-chronically exposed to the same conditions as described in this work [30,39]. These histopathological alterations were also consistent with the exposure route and the time of euthanization.…”
Section: Resultssupporting
confidence: 84%
“…The highest liver CYN-immunopositivity correlates with the histopathological lesions described by light and electron microscopy in tilapia ( O. niloticus ) acutely and sub-chronically exposed to the same conditions as described in this work [30,39]. These histopathological alterations were also consistent with the exposure route and the time of euthanization.…”
Section: Resultssupporting
confidence: 84%
“…The latter observation however is disputable N o n -c o m m e r c i a l u s e o n l y as no studies on isolated cultures of this cyanobacterium were performed. Complementary studies have been recently conducted on the toxicity of CYN (Guzmán-Guillén et al, 2015;Sierosławska et al, 2015;), mechanisms of toxicity , biodegradation (Dziga et al, 2016) and biological role and allelopathy (B-Béres et al, 2015). These works have contributed valuable knowledge on these aspects but at the same time have revealed many gaps in understanding of the role(s) of CYN in aquatic ecosystems and its impact on their functioning (Sukenik et al, 2015).…”
Section: Occurrence Of Cyanobacteria and Cyanotoxins And Methods Formentioning
confidence: 99%
“…However, for the kidney, contradictory results have been described, showing decreased cross‐sections of proximal and distal convoluted tubules (DCT) in fish exposed to pure CYN by oral and i.p. injection, specially after 5 days of exposure (Gutiérrez‐Praena et al, ), whereas Guzmán‐Guillén et al () found increases in this parameter after 7 days of exposure and decreases after 14 days.…”
Section: Introductionmentioning
confidence: 98%
“…Among the morphological changes, disorganized parenchymal architecture in the liver and light degenerative processes, dilated Bowman's space, glomerular capillary atrophy and hyperemia in the kidney, fibrolysis with marked edema in the heart, necrotic enteritis in the intestines, and tumefaction and hemorrhages in the gills, were reported for fish acutely exposed to pure CYN orally (Puerto et al, ), by intraperitoneal (i.p.) injection (Gutiérrez‐Praena et al, ), or subchronically exposed to cyanobacterial cells containing CYN by immersion (Guzmán‐Guillén et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation